Transport of a colloidal particle driven across a temporally oscillating optical potential energy landscape - Abbott, J; Straube, A; Aarts, D; Dullens, R (IOP Science, 2019)
A colloidal particle is driven across a temporally oscillating onedimensional optical potential energy landscape and their particle motion is analysed. Different modes of dynamic mode locking are observed and are confirmed with the use of phase portraits. The effect of the oscillation frequency on the mode locked step width is addressed and the results are discussed in light of a high frequency theory and compared to simulations. Furthermore, the influence of the coupling between the particle and the optical landscape on mode locking is probed by increasing the maximum depth of the optical landscape. Stronger coupling is seen to increase the width of mode locked steps. Finally, transport across the temporally oscillating landscape is studied by measuring the effective diffusion coefficient of a mobile particle, which is seen to be highly sensitive to the driving velocity and mode locking.